(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to analyze the impact of mobile banking services on the financial performance of commercial banks by examining the main concepts related to digital banking services and financial performance, and by clarifying the relationship between them in light of the rapid digital transformation in the banking sector. The study adopted a descriptive-analytical approach based on reviewing relevant literature and previous studies. The findings revealed that mobile banking services are one of the most important tools of digital transformation that contribute to improving banks’ financial performance by reducing operational costs, increasing operational efficiency, and enhancing customer satisfaction, which positively reflects on profitability and efficiency indicators. The study also showed that the success of these services depends on the availability of technological infrastructure, security level, and customer acceptance of technology. The study recommended the need to enhance investment in mobile banking services and further develop them in line with modern technological advancements to achieve better financial performance for commercial banks.